MUHAMMADIYAH AND URBAN MUSLIM GENDER EQUALITY ISSUES: NEO-TRADITIONALISM IN THE DECISION OF THE MAJELIS TARJIH AND TAJDID MUHAMMADIYAH ON HUSBAND AND WIFE RELATIONSHIP - Falah, Mohammad Bachrul; Riyanta, Riyanta; Maliki, Ibnu Akbar (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2024)
The religious authority held by Islamic institutions is often confronted with issues of gender discrimination. In the modern era, Islamic organizations are faced with gender problems related to husband-wife relations in urban muslim communities. The proliferation of gender-biased narratives on social media and the shift in religious authority has challenged the discourse on gender equality in urban muslim communities. Meanwhile, in its development, Islamic organizations have produced progressive fatwas that show the movement for gender justice. This research uses Equilibrium Theory to analyze the periodic decisions of the Majelis Tarjih and Tajdid Muhammadiyah regarding the relationship between husband and wife. The results of the decision will be categorized through the typology of Islamic thought according to Ziba Mr-Hossen. This research is literature research that uses primary data in the form of decisions of the Majelis Tarjih and Tajdid Muhammadiyah compiled in Adāb al-Mar'ah fi al-Islām in 1982 and Keluarga Sakinah in 2014. The data was collected using the documentation method and analyzed using the content analysis technique. The results showed that the discourse of gender equality in Muhammadiyah influenced the balance of husband and wife roles in the Sakinah Family decision. The influence of gender equality does not necessarily make the results of the Sakinah Family decision fall into the category of modernism that is very open to Western thought. However, the decision only reaches the typology of neotraditionalism as a reflection of the moderatism of thought. The reason is that the fatwa decision still adopts the thoughts of classical scholars while still carrying the theme of renewal (tajdīd). Through its ijtihād, Muhammadiyah can create an inclusive dialogue space, accommodate various perspectives, and reflect the spirit of justice in the context of the diversity of urban muslim communities. This research is expected to be a symbol of dialogue between the discourse of gender equality and traditional religious authorities so that the dialectic can produce fatwas that are by the times.